Optimasi Biaya Distribusi Semen Menggunakan Uji Optimal Metode Stepping Stone Dan Metode Medified Distribution (MODI) - Yosefina Mouria Vainy Liefofid; Inanty Mulia Sentry; Cindy Malinda Uscha (Lembaga Pengembangan Kinerja Dosen, 2023)
TB. Medang Indah is a building materials store located in Medang, Tangerang Regency, Banten which has been established since 2008. This study aims to obtain optimal transportation costs with an effective route in distributing cement to TB. Medang Indah. To achieve the objectives of this research, several steps were carried out, namely, by creating a transportation model from the data obtained, determining the initial solution using the Vogel's Approximation (VAM) method, and determining the optimal solution using two methods, namely the Stepping Stone method and the Modified Distribution (MODI) method. From determining the initial solution of Rp. 52,460,000.00 and the optimal solution from both methods has the same cost and route, which is Rp. 52,350,000.00. This indicates that the route to be used by TB. Medang Indah in optimizing costs with efficient routes, namely Rp. 52,350,000.00.